Peningkatan Keterampilan Mengajar Melalui Supervisi Akademik Dengan Pendekatan Lesson Study Pada Guru Kelas Awal MI Ma’arif Karangtengah - Nadlirotul Muniroh (THE JOER: Journal Of Education Research, 2022)
This study aims to identify and analyze: This study aims to: (1) Improve the teaching skills of teachers through academic supervision. (2) Improving the teaching skills of early grade teachers through a lesson study approach at MI Ma'arif Karangtengah in Semester 2 of the 2018/2019 Academic Year. (3) Improving the learning outcomes of early grade students by choosing the appropriate approach. The type of research is School Action Research. The research subjects were Class 1, 2 and 3 MI Ma'arif Karangtengah teachers, Tuntang District in 2019, totaling 3 people, consisting of 2 boys and 1 girl. Data collection techniques using observation / study documents and interviews. The data analysis technique used descriptive analysis. Based on the results of the research and discussion, it can be concluded: (1) The lesson study model can improve the skills of managing thematic learning of grade 1, 2, and 3 teachers at MI Ma'arif Karangtengah, Tuntang District, Semarang Regency in the second semester of the 2018/2019 academic year. (2) The magnitude of the increase in skills in managing thematic learning of grade 1, 2, and 3 MI Ma'arif Karangtengah teachers, Tuntang District, Semarang Regency in the second semester of the 2018/2019 academic year is as follows: (a) Planning = 29.75%; (b) Learning = 22.9%; and (c) an average of 26.3%.